“Despartares Decoloniales”: The Implications of “Territorio Cuerpo-Tierra” for Studying Women's Embodied Resilience to Trauma in El Salvador, Central America - Liegghio, Maria (Violence against women, 2025)
We explore the implications of the concept of territorio cuerpo-tierra for conducting research on women's resilience to trauma and post-COVID-19 pandemic recovery in El Salvador, Central America. Cuerpo-territorio forces a reconceptualization of women's realities as bound to the embodiment of the geo-politics of gender, body, and land as territories, and thus, their realities as bound to the histories and temporality of those as territories. Through a series of despartares decoloniales (decolonial awakenings), we postulate that resilience research reproduces narrowly defined understanding of women's realities and responses to both the symbolic and physical conditions and adversities of their lives.